AB1059 A RANDOMIZED, PLACEBO-CONTROLLED STUDY OF ANAKINRA IN PATIENTS WITH STILL´S DISEASE. (2nd June 2020) - Schanberg, L.; Nigrovic, P.; Cooper, A.; Chatham, W.; Akoghlanian, S.; Singh, N.; Rabinovich, E.; Thatayatikom, A.; Taxter, A.; Hausmann, J.; Zdravkovic, M.; Ohlman, S.; et al.
Abstract : Background: Adult-onset Still's disease (AOSD) and systemic juvenile idiopathic arthritis (SJIA) are rare autoinflammatory disorders associated with an activated IL-1 pathway, characterized by spiking fever, rash, arthritis, lymphadenopathy, hepatosplenomegaly and serositis. There is a growing understanding that SJIA and AOSD are one disease with different ages of onset, i.e. Still's disease. The anaSTILLs study (ana kinra in Still´s disease) was designed to further evaluate efficacy and safety of anakinra in patients with Still´s disease across all age groups. Objectives: The primary objective was to demonstrate efficacy of anakinra versus placebo as assessed by ACR30 response with absence of fever at Week 2. Secondary objectives included: early onset of efficacy, sustained efficacy, time to study drug discontinuation, safety, pharmacokinetics, clinical signs and biomarkers. Methods: 'anaSTILLs' was a randomized, double-blind, placebo-controlled, 12-week study including patients with active and newly diagnosed (6 months) Still´s disease according to adapted ILAR criteria if <16, or Yamaguchi criteria, if ≥16 years of age at disease onset. Patients were randomized to anakinra 2 mg/kg (max 100 mg/day), 4 mg/kg (max 200 mg/day) or placebo. Results: 12 patients were randomized and received study drug: 6 anakinra (2 mg/kg n=2, 4 mg/kg n=4) and 6 placebo, the study was terminated early due to slow recruitment. 1 patient on placebo had lymphoma, not Still's disease, and was excluded; thus in total 11 patients were analyzed for efficacy, 8 were children [median (range) age=4.0 (1-11) years] and 3 were adults [median (range) age=32.0 (25-51) years]. 55% were male and the mean symptom duration was 74.2 days. All patients on anakinra but none on placebo achieved ACR30 response with absence of fever at Week 2 (p-value=0.0022). The efficacy of anakinra was further demonstrated by superiority to placebo in ACR50/70/90 responses with absence of fever at Week 2. All placebo patients discontinued the study within 6 weeks, 2 due to progressive disease, 2 due to lack of efficacy and 1 due to withdrawal by patient. There was a numerically higher proportion with early onset of efficacy (Week 1) in the anakinra group compared to placebo. The ACR30/50/70/90 responses in the anakinra group were sustained throughout the study period. Patients in the anakinra group had a prompt and persistent decrease in CRP and ferritin levels at Week 1, which was not observed in the placebo group. There were no unexpected safety findings. All anakinra patients developed anti-drug antibodies (ADAs) at some timepoint during the study. ADAs were persistent throughout the treatment period, except in one patient. Titers were low to moderate. One placebo patient had low ADA titers at one occasion. No neutralizing antibodies were observed and the ADAs did not appear to impact clinical efficacy or safety. Conclusion: Anakinra is superior to placebo in the treatment of Still's disease. ADAs occur frequently but do not appear to adversely impact efficacy or safety. These results confirm the benefits of anakinra treatment in patients with active, newly diagnosed Still´s disease across ages. Disclosure of Interests: Laura Schanberg Grant/research support from: Sobi, BMS, Consultant of: Aurinia, UCB, Sanofi, Peter Nigrovic Grant/research support from: Novartis, BMS, Pfizer, Consultant of: Novartis, BMS, Pfizer, Sobi, Miach Orthopedics, Simcere, XBiotech, Quench Bio, Ashley Cooper: None declared, Winn Chatham Grant/research support from: Sobi, Consultant of: Sobi, Shoghik Akoghlanian: None declared, Namrata Singh: None declared, Egla Rabinovich Grant/research support from: AbbVie, UCB Pharma, Janssen Research & Development, Akaluck Thatayatikom: None declared, Alysha Taxter: None declared, Jonathan Hausmann Consultant of: Novartis, Milan Zdravkovic Shareholder of: Sobi, Employee of: Sobi, Sven Ohlman Shareholder of: Sobi, Employee of: Former employee of Sobi, Henrik Andersson Employee of: Sobi, Susanna Cederholm Shareholder of: Sobi, Employee of: Sobi, Margareta Wikén Shareholder of: Sobi, Employee of: Former employee of Sobi, Rayfel Schneider Grant/research support from: Roche, Novartis, Sobi, Pfizer, Consultant of: Sobi, Novartis, Novimmune, Fabrizio De Benedetti Grant/research support from: AbbVie, Pfizer, Novartis, Novimmune, Sobi, Sanofi, Roche, Speakers bureau: AbbVie, Novartis, Roche, Sobi